Risk factors associated with the stability of mini-implants and mini-plates: systematic review and meta-analysis - Mattos, Paola; Gonçalves, Flavio; Basso, Isabela; Zeigelboim, Bianca; Niwa, Marcio; Neto, José; Santos, Rosane Sampaio; Araujo, Cristiano; Guariza‑Filho, Odilon (Springer, 2021)
Objective: The objective of this systematic review is to assess the risk factors associated with the stability of mini-implants and mini-plates in patients undergoing orthodontic treatment using temporary anchorage devices. Material and Methods: Search strategies were developed for each electronic database (PubMed/Medline, LILACS, Scopus, Web of Science, Embase, and Cochrane Library) and gray literature (Google Scholar, Proquest, and Open Grey). The risk of bias was assessed using the Cochrane Collaboration tool for assessing the risk of bias and Meta-Analysis of Statistics Assessment and Review Instrument. The certainty of the evidence was assessed using the GRADE tool. Meta-analyses and meta-regressions of random effects were performed for the outcomes of interest. Results: A total of 1517 articles were found, of which seven were selected for quantitative synthesis. When comparing the risk of failure between mini-implants and mini-plates, the risk values approached the threshold of statistical significance (p = 0.07) (RR = 1.83; 95% CI = 0.96–3.50; I2 = 69%), showing significance after sensitivity analysis (p < 0.05) and a greater risk for mini-implants. Mandible installation presented a higher risk of failure (RR = 1.85; 95% CI = 1.17–2.91). Conclusions: The evidence found indicates that failure in the stability is related to the type of device and that there is a greater risk by using isolated mini-implants, especially when positioned in the mandible. Clinical relevance: These findings help the orthodontist and/or the surgeon to stipulate risks, learn about the predictability of techniques, and communicate with the patient in an easier way.
Keywords: Temporary anchoring devices; Mini-implant; Mini-plate; Stability; Systematic review